Tattoos, piercings, and symptoms of ADHD in non-clinical adults: a cross-sectional study - Glans, Martin Ragnar; Nilsson, Joel; Bejerot, Susanne (Frontiers in Psychiatry, 2024)
Introduction: Tattoos and piercings are associated with impulsive and risk-taking personality traits, characteristics that are also common along the ADHD continuum. However, studies on ADHD and body modification are lacking. Thus, our aims were to assess the association between body modification and subclinical ADHD symptom severity, and to investigate if body modification can serve as an indication for ADHD examination.Methods: 762 adults (529 women and 233 men) without diagnosis of ADHD completed the Adult ADHD self-report scale (ASRS) and answered questions concerning body modification. Two different ASRS versions were utilized; the 18-item ASRS Symptom Checklist and the 6item ASRS Screener. Three categorizations of body modifications were analysed: i) having at least one tattoo ii) having at least one piercing other than ear piercing iii) the combination of simultaneously at least one tattoo and one piercing. Mean 18-item ASRS total-and subscale scores and the proportion of positive results on the 6-item ASRS Screener were compared between those with and those without body modification, while adjusting for covariates age and sex. Additional analyses were performed for ≥2 and ≥3 body modifications.In our cohort, 26% had a tattoo, 14% had a piercing other than ear piercing and 8% had a combination of tattoo and piercing. Having any kind of body modification was associated with more pronounced symptoms of ADHD and with a cut-off score on the ASRS Screener indicating ADHD. Whereas the effect sizes were small for tattoos, medium to large effect sizes were seen for ≥2 piercings in the ASRS. Also, moderately strong associations emerged for ≥1 piercing and a positive ASRS screening result.Our results suggest that acquiring a body modification, especially a tattoo, is entering the mainstream in Sweden. Correspondingly, differences in subclinical ADHD symptomatology between non-clinical adults with and without body modifications are subtle. Having ≥2 piercings other than ear piercing on the other hand, is associated with clinically relevant differences in ADHD symptoms. Moreover, piercing status may serve as an indicator, among others, for further ADHD assessments. However, more research is needed to ascertain possible signalling functions of body modifications in clinical settings.